2017
DOI: 10.1016/j.bjoms.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Potential of autogenous or fresh-frozen allogeneic bone block grafts for bone remodelling: a histological, histometrical, and immunohistochemical analysis in rabbits

Abstract: Our aim was to compare the wound healing of autogenous bone grafts with that of fresh-frozen allogeneic block bone in rabbits. We used 25 animals. One was killed before the experiment to provide the allogeneic bone, and the remainder were killed at four time points (n=6 in each group). On histometrical analysis there was a significant difference between the two groups only at 45days and between 15 and 45days in the intergroup analysis. However, there was significantly more revascularisation (p<0.05), resorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Moreover, a randomized controlled trial assessing HARA with FFA compared with autogenous bone block revealed new bone formation with both treatment modalities, but FFA demonstrated clear signs of inflammation [20]. Similar healing patterns have been observed in an experimental study demonstrating statistically significant greater revascularization and bony replacement after HARA with autogenous bone block compared with allogeneic bone block [63].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Moreover, a randomized controlled trial assessing HARA with FFA compared with autogenous bone block revealed new bone formation with both treatment modalities, but FFA demonstrated clear signs of inflammation [20]. Similar healing patterns have been observed in an experimental study demonstrating statistically significant greater revascularization and bony replacement after HARA with autogenous bone block compared with allogeneic bone block [63].…”
Section: Discussionsupporting
confidence: 56%
“…Autogenous bone block was replaced by newly formed bone, whereas regions of non-vital bone were seen after HARA with allogeneic bone block [63]. Consequently, both treatment modalities seem to facilitate new bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Junior and colleagues reported that dehiscence may occur on the implant surface even after a lengthy healing period due to nonvascularized tissue areas supported by allogenic grafts. They also suggested that complete revascularization is never possible in allogenic block grafts, and even after a long time, necrotic areas may be present at the application site 31. In a study, implants were followed for 30 to 35 years, and allograft was preferred as the graft material for bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…In another study in animal, when they compared the allogeneic block graft with the autogenic block graft, they reported that there were necrotic areas in the allogeneic group even after 180 days, which may be due to the delay in the first revascularization, but the autogenic group was completely revascularized after 180 days and there were no necrotic areas. Junior et al 13 also reported that the necrotic, non-vascularized tissue areas in their implants supported by allogeneic graft may create conditions for the formation of bone sequestration areas later, and may cause openings on the surface of the implant even after a long period of application, and complete removal of the block graft will be required. In addition, they suggest that the allogeneic block graft can never be completely revascularized and necrotic areas will remain even after a long time.…”
Section: Discussionmentioning
confidence: 99%